Alterações fonoarticulatórias em indivíduos com neurofibromatose tipo 1 - Carla Menezes da Silva (2013)
Introduction: The neurofibromatosis (NF) is the name given to a group of diseases caused by genetic mutations classified as neurofibromatosis type 1, neurofibromatosis type 2 and the schwanomatose. Among them, the neurofibromatosis type 1(NF1) stands out because it is one of the most frequent genetic alteration in the human being. The NF1 is characterized by neurocutaneous lesions with coffee and milk colored skin spots, auxiliary and inguinal similar ephelides, cutaneous neurofibromas, Lish nodules and bone dysplasia. The clinical manifestations have been considered, in most cases, discreet and benign, but with a possibility of a multisystem incase besides behavior and cognitive alterations which can interfere in the psychosocial learning and development. Besides these abnormalities, a preliminary study carried out at the Minas Gerais Neurofibromatosis Reference Center (CRNF-MG) observed speech alterations in about 40% of the individuals with NF1 characterized by dysphonia, articulatory imprecision and hypernasality. Objective: Evaluate and compare the speech articulatory structures of individuals with NF1 with volunteers without the disease and correlate them concerning the global muscular force. Case Studies and Methods: A sample of 24 patients with NF1 treated at CRNF-MG and 24 volunteers without the disease were evaluated concerning: manual maximum gripping (Fmax) through the hand-grip technique, oral facial motor function and voice through the MBGR protocol (Marchesan, Berrentin-Felix, Genaro, Rehder) and the electrical potential of the masseter muscle through the superficial electromyography. Results: The individuals with NF1 showed a smaller Fmax than the control ones, and this difference was greater in the male individuals. The main findings in this study show that the individuals with NF1 presented a greater prevalence of alterations in the speech articulatory structures and significant differences (p < 0.05) when compared to the control group concerning body and speech articulatory structures posture, mobility, tonus, pain upon palpation and stomatognathic roles. The total test score also showed a significant Spearman correlation coefficient with a significant level lower than 5% in relation to Fmax. Conclusion: The individuals with NF1 showed more speech articulatory alterations than the volunteers without the disease, and these alterations were associated to the reduction of the global muscular force. The oral facial mobility and voice alterations represent an important commitment of the communicative ability of individuals with NF1 with a negative impact in their life quality. Therefore, it is possible that an early speech therapy intervention aiming at increasing the muscular force of the oral facial structures can contribute to attenuate the speech articulatory difficulties of this population mainly in their communication effectiveness and functionality.